Association Between Poor Sleep, Fatigue, and Safety Outcomes in Emergency Medical Services Providers - P. Daniel Patterson; Matthew D. Weaver; R Frank; Charles W. Warner; Christian Martin‐Gill; Francis X. Guyette; Rollin J. Fairbanks; Michael W. Hubble; Thomas J. Songer; Clifton W. Callaway; Sheryl F. Kelsey; David Hostler (2012)
To determine the association between poor sleep quality, fatigue, and self-reported safety outcomes among emergency medical services (EMS) workers.We used convenience sampling of EMS agencies and a cross-sectional survey design. We administered the 19-item Pittsburgh Sleep Quality Index (PSQI), 11-item Chalder Fatigue Questionnaire (CFQ), and 44-item EMS Safety Inventory (EMS-SI) to measure sleep quality, fatigue, and safety outcomes, respectively. We used a consensus process to develop the EMS-SI, which was designed to capture three composite measurements of EMS worker injury, medical errors and adverse events (AEs), and safety-compromising behaviors. We used hierarchical logistic regression to test the association between poor sleep quality, fatigue, and three composite measures of EMS worker safety outcomes.We received 547 surveys from 30 EMS agencies (a 35.6% mean agency response rate). The mean PSQI score exceeded the benchmark for poor sleep (6.9, 95% confidence interval [CI] 6.6, 7.2). More than half of the respondents were classified as fatigued (55%, 95% CI 50.7, 59.3). Eighteen percent of the respondents reported an injury (17.8%, 95% CI 13.5, 22.1), 41% reported a medical error or AE (41.1%, 95% CI 36.8, 45.4), and 90% reported a safety-compromising behavior (89.6%, 95% CI 87, 92). After controlling for confounding, we identified 1.9 greater odds of injury (95% CI 1.1, 3.3), 2.2 greater odds of medical error or AE (95% CI 1.4, 3.3), and 3.6 greater odds of safety-compromising behavior (95% CI 1.5, 8.3) among fatigued respondents versus nonfatigued respondents.In this sample of EMS workers, poor sleep quality and fatigue are common. We provide preliminary evidence of an association between sleep quality, fatigue, and safety outcomes.